2012
DOI: 10.1103/physrevlett.109.103602
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Rayleigh Lithography Using High Flux Loss-Resistant Entangled States of Light

Abstract: Quantum lithography achieves phase superresolution using fragile, experimentally challenging entangled states of light. We propose a scalable scheme for creating features narrower than classically achievable with reduced use of quantum resources and, consequently, enhanced resistance to loss. The scheme is an implementation of interferometric lithography using a mixture of a spontaneous parametric down-converted entangled state with intense classical coherent light. We measure coincidences of up to four photon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Our N00N-state source can produce high-fidelity, high-N N00N states [15,16,19], and we have shown that the N00N state OCM signal displays N-fold super-resolution with a visibility that is nearly independent of N. Thus, our implementation is naturally applicable to higher photon numbers. This could be achieved using several exciting new technologies which are continually advancing, such as high-efficiency single-photon detectors [20,21], high-fill-factor single-photon detector arrays [22], and brighter down-conversion sources with high coupling efficiency [23][24][25].…”
Section: Fig 3 Experimentally Measured Centroids For One To Four Phmentioning
confidence: 83%
See 1 more Smart Citation
“…Our N00N-state source can produce high-fidelity, high-N N00N states [15,16,19], and we have shown that the N00N state OCM signal displays N-fold super-resolution with a visibility that is nearly independent of N. Thus, our implementation is naturally applicable to higher photon numbers. This could be achieved using several exciting new technologies which are continually advancing, such as high-efficiency single-photon detectors [20,21], high-fill-factor single-photon detector arrays [22], and brighter down-conversion sources with high coupling efficiency [23][24][25].…”
Section: Fig 3 Experimentally Measured Centroids For One To Four Phmentioning
confidence: 83%
“…Making this four-photon state requires that the laser two-photon rate be three times larger than the DC two-photon rate. However, even if the laser rate is further increased, increasing the four-photon count rate, the fidelity of the four-photon state will not be significantly degraded [19]. To make four-photon N00N states, we choose to make the laser two-photon rate 8.5 times larger than the DC rate (configuration 2), which leads to a fidelity with the ideal state of 85%, a theoretical OCM visibility of 85%, and increases the four-photon rate by about a factor of 10 (compared to the configuration in which the four-photon fidelity is optimized).…”
mentioning
confidence: 99%
“…Our N00N-state source produces high-fidelity, high-N N00N PRL 112, 223602 (2014) P H Y S I C A L R E V I E W L E T T E R S week ending 6 JUNE 2014 states [15,16,20], and we have shown that the N00N state OCM signal displays N-fold superresolution, and a visibility that is nearly independent of N. Thus, our implementation is naturally applicable to higher photon numbers. This could be achieved using several exciting new technologies which are continually advancing, such as high-efficiency single-photon detectors [23,24], high-fillfactor single-photon detector arrays [25], and brighter down-conversion sources with high coupling efficiency [21,22].…”
Section: Prl 112 223602 (2014) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 88%
“…This requires that the laser twophoton rate be three times larger than the DC two-photon rate. However, even if the laser rate is further increased, increasing the four-photon count rate, the fidelity of the four-photon state will not be significantly degraded [20]. To make four-photon N00N states, we choose to make the laser two-photon rate 8.5 times larger than the DC rate (configuration 2), which leads to a fidelity with the ideal state of 85%, a theoretical OCM visibility of 85%, and increases the four-photon rate by about a factor of 10 (compared to the configuration in which the four-photon fidelity is optimized).…”
Section: Prl 112 223602 (2014) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…The sensitivity of the displacement x can therefore be improved by preparing a Schrödinger cat state of the momentum p. The N00N state composed by two optical modes with opposite momenta seems to be a good candidate, but the fragile high photon number N00N state is very difficult to prepare, to preserve, and to manipulate [21][22][23][24][25][26][27]. On the other hand, a single photon can be easily prepared in an entangled state of two oppo- [28].…”
mentioning
confidence: 99%